Adhesion study for a composite system - Tien, Shawn Wei Chong (2014)
The objective of this Final Year Project (FYP) was to optimise the adhesion within a ceramic – composite system in defence applications. Building on the discovery of poor adhesion in the system during the Industrial Attachment with the company, testing, research and development was done on adhesives and treatment methods that would increase the adhesive strength in the system. Bonding tests which included tensile, flexural and lap shear testing were conducted on Ceramic A tiles, Polymer B and Polymer C composites using a range of adhesives. Also, two surface treatment methods, namely bromination and GFRP, were carried out in this FYP. It was found that epoxy-based adhesives had the highest bonding and shear strength values with LA3 being the highest. However, it had a rigid bonding interface which produced brittle failure. In the lap shear tests, Polymer B composites had better adhesion as compared to Polymer C composites when tested on Ceramic A tiles. Comparing surface treatment methods, bromination saw varied success with increased adhesion and shear strength only seen in LA2 out of the three epoxy-based adhesives tested whereas the introduction of GFRP in adhesives saw a marked decrease in adhesive strength during tensile and flexural testing but had an increase in shear strength in the lap shear testing with the use of epoxy-based adhesives. GFRP had also made the failure less brittle in nature.